Two Cases of Severe Hypertension in JAK2 Mutation-Positive Myeloproliferative Neoplasms - Raunak Rao; Spoorthy Kulkarni; Ian B. Wilkinson (Case Reports in Vascular Medicine)
Background. Myeloproliferative neoplasms are a heterogeneous group of disorders resulting from the abnormal proliferation of one or more terminal myeloid cells—established complications include thrombosis and haemorrhagic events; however, there is limited evidence to suggest an association with arterial hypertension. Herein, we report two independent cases of severe hypertension in JAK2 mutation-positive myeloproliferative neoplasms. Case Presentations. Case 1: a 39-year-old male was referred to our specialist hypertension unit with high blood pressure (BP) (200/120 mmHg), erythromelalgia, and headaches. We recorded elevated serum creatinine levels (146 μM) and panmyelosis. Bone marrow biopsy confirmed JAK2-mutation-positive polycythaemia vera. Renal imaging revealed renal artery stenosis. Aspirin, long-acting nifedipine, interferon-alpha 2A, and renal artery angioplasty were employed in management. BP reached below target levels to an average of 119/88 mmHg. Renal parameters normalised gradually alongside BP. Case 2: a 45-year-old male presented with high BP (208/131 mmHg), acrocyanosis, (vasculitic) skin rashes, and nonhealing ulcers. Fundoscopy showed optic disc blurring in the left eye and full blood count revealed thrombocytosis. Bone marrow biopsy confirmed JAK2-mutation-positive essential thrombocytosis. No renal artery stenosis was found. Cardiac output was measured at 5 L/min using an inert gas rebreathing method, providing an estimated peripheral vascular resistance of 1840 dynes/s/cm5. BP was well-controlled (reaching 130/70 mmHg) with CCBs. Conclusions. These presentations highlight the utility of full blood count analysis in patients with severe hypertension. Hyperviscosity and constitutive JAK-STAT activation are amongst the proposed pathophysiology linking myeloproliferative neoplasms and hypertension. Further experimental and clinical research is necessary to identify and understand possible interactions between BP and myeloproliferative neoplasms.